2015
DOI: 10.7863/ultra.34.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Diagnostic Indices Comprising Clinical, Sonographic, and Biomarker Data for Discriminating Benign From Malignant Ovarian Masses

Abstract: The objective of this study was to review the accuracy of indices combining several diagnostic variables, in comparison to other models, sonography alone, and biomarker assays, for predicting benign or malignant ovarian lesions. Different single modalities were reviewed. The most useful complex models were International Ovarian Tumor Analysis (IOTA) sonographic logistic regression model 2 (area under the curve, 0.949), risk of malignancy index-cancer antigen 125-human epididymis protein 4 (0.950), risk of mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Our systematic review addresses several issues in existing systematic reviews. As part of a scoping review, 10 original systematic reviews were identified up to 2021, [ 9 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] NICE 2011; 6 of 11 reviews included ROMA, 7 RMI I. The most recent review search date was 2018 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review addresses several issues in existing systematic reviews. As part of a scoping review, 10 original systematic reviews were identified up to 2021, [ 9 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] NICE 2011; 6 of 11 reviews included ROMA, 7 RMI I. The most recent review search date was 2018 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical appearing simple cysts have a 0%-1% risk of cancer, and typical hemorrhagic cysts, endometriomas, and dermoids have a 1%-2% risk of cancer (7)(8)(9)(10)(11)(12)(13)(14). Conversely, adnexal cysts with a vascularized soft-tissue component are considered to have a high probability of ovarian cancer (5,7,(15)(16)(17)(18)(19)(20)(21). In between the two ends of the spectrum are cysts that cannot be definitively characterized as probably benign or possibly malignant, and they are considered indeterminate at US.…”
Section: Subjects and Inclusionmentioning
confidence: 99%
“…As a result, combining color Doppler imaging with pulsed Doppler spectrum analysis improves ovarian mass characterization by obtaining quantitative measurement of blood flow from tumor vessels, increasing the specificity & sensitivity of ovarian mass characterization 8 . The rationale of the study, to find the frequency of ovarian cyst observed in Doppler ultrasound.…”
Section: Introductionmentioning
confidence: 99%